Numerical study of formation of a series of bubbles at a submerged orifice - Chen, Xiyu; Chen, Nan; Delgado, Antonio (Applied Mathematical Modelling, 2019)
Bubble formation from a submerged orifice is widely applied in bio-process and chemical reaction systems. In this study, the effects of different orifice diameters and contact angles in Period-I and Period-II regimes are studied systematically on a 2D axisymmetric domain. Simulation results are presented from the formation of the first bubble and explained by means of the surrounding fluid field, bubble interaction, and bubble aspect ratio. The orifice diameter is varied from 0.6 mm to 3 mm. The numerical results show that the detachment time of all bubbles remains constant (in time) for smaller orifice diameters (d a ≤ 1.5 mm), while the detachment time of the first bubble is different from the rest of the bubbles for larger orifice diameters (d a ≥ 2 mm), which is due to the different surrounding flow field. Contact angles from 60° to 165° are considered for the gas flow rates in the regime of bubble pairing, and it is observed that the bubble detachment time decreases when the contact angle increases, and it converges to a constant value when the contact angle is larger than 135°. In addition, the transition from period doubling to deterministic chaos (in which there is a variable number of bubbles within each period) is observed. A new scenario of inserting a submerged tube upward into the liquid is considered and compared to the previous cases. It is observed that when the tube is vertically inserted into the liquid, the bubble detachment time is even smaller because of higher influence from the surrounding liquid field, leading to a different phenomenon from the non-inserted tube cases.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Aspect ratio; Bubble; Cascade to chaos; Contact angle; Detachment time; Period doubling